Menstrual Hygiene Practices amongst Reproductive Age Group Females Visiting a Tertiary Care Hospital, Lahore - Rozina Shahdat KHAN; Sarah Khalid; Mubeen Saeed; Michelle Gillani (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To assess the menstrual hygiene practices in relation to age, educational level, marital status and residence among the females of reproductive age group attending Gynae OPD of LGH. Methods: This cross sectional comparative study was conducted amongst conveniently selected 385 reproductive age group females. Questionnaire was developed and Data entry , analysis  done using SPSS version 25.0. Scoring system was developed allocating 0 to 2 score for individual variable with a total score of 24 for the 12 variables of Menstrual hygiene practices. Chi-square test of Significance was used to find relation between age, educational level, marital status and residence with menstrual hygiene practices. Results: Majority (61.6%) were between 21-30 years. Educational status of majority females (31.2%) was primary/middle pass followed by 31.2% matric pass females. Married females were 293/385 (76.1%). Majority of females 202/385 (52.5%) attending Gynae OPD were from Main city Lahore. Mean score for menstrual hygiene practices remained 19.2169 with minimum to maximum of 9.50 (0.3%) to 24 (4.4%). Only 232/385(60.26%) who opted exclusive menstrual hygiene practices had mean scoring of  21.75 mean with minimum  to maximum  scoring of 19 to 24 respectively. Significant relationship was found between Residence, Education and Menstrual Hygiene practices. Conclusion: only 59.5% achieved exclusive use of hygienic methods during menstruation. Surprisingly 3.17% females of intermediate level education were using cloth as absorbent material during menstruation, out of which 66.67% were from peripheral Lahore suggestive of place of living impacting more than education most probably due to non-availability of other absorbents or financial constraints amongst educated females.